The intake of a hazelnut skin extract improves the plasma lipid profile and reduces the lithocholic/deoxycholic bile acid faecal ratio, a risk factor for colon cancer, in hamsters fed a high-fat diet. (15th January 2015) - Caimari, Antoni; Puiggròs, Francesc; Suárez, Manuel; Crescenti, Anna; Laos, Sirle; Ruiz, Juan Antonio; Alonso, Virginia; Moragas, Josep; del Bas, Josep Maria; Arola, Lluís
Highlights: A hazelnut skin extract, FIBEROX™ (FBX), exhibited blood lipid-lowering effects. Fiber, polyphenols and phytosterols can contribute to these hypolipidemic effects. Cholesterol-lowering effects may be due to the activation of faecal bile acid excretion. FBX drops the faecal lithocholic/deoxycholic acid ratio, a colon cancer risk factor. FBX could be considered as a new potential functional food ingredient. Abstract: The effects on lipid and glucose metabolism of a hazelnut skin extract (FIBEROX™) administrated during 8 weeks (HFD-FBX8w group) or during the last 4 weeks of the study (HFD-FBX4w group) to Golden Syrian hamsters fed a high-fat diet (HFD) for 8 weeks were investigated. FIBEROX™ consumption reversed the increase in total and LDL plasma cholesterol induced by the HFD feeding in both HFD-FBX groups and decreased the circulating levels of free fatty acids and triglycerides in the HFD-FBX4w animals. The higher excretion of bile acids found in the faeces of both groups of hamsters fed the FIBEROX™ suggests that this mechanism is involved in the cholesterol-lowering effects of the extract. Furthermore, FIBEROX™ intake sharply decreased the lithocholic/deoxycholic bile acid faecal ratio, a risk factor for colon cancer, in both HFD-FBX groups. In conclusion, the consumption of FIBEROX™ improves different risk factors associated with cardiovascular disease and colon cancer.